The use of audio-biographical cues in dementia care: a four-year evaluation in Swiss hospitals, care, and domestic homes - Edwards, Heather; Oppikofer, Sandra; Aschwanden, Damaris (Frontiers in Dementia, 2024)
Introduction In dementia care, the integration of innovative interventions is essential to enhancing the wellbeing and quality of life of people with dementia. Among these interventions, the Music Mirror intervention has emerged as a promising tool to provide personalized audio-biographical cues aimed at soothing, motivating, and engaging people with dementia. This study examined the effects of a Music Mirror intervention on the (a) wellbeing, emotions, and behavioral and psychological symptoms of 155 individuals with dementia, (b) perceived burden, relationship quality, and gains of their informal/formal caregivers, and (c) momentary closeness, wellbeing and stress of caregivers. Methods This four-year study employed a quasi-experimental waiting-control group design, utilizing before-after measurements in Swiss hospitals, care homes, and domestic homes. For four 6-week intervention phases, Music Mirrors, i.e., brief written resources of acoustic material, associated with practical activities of daily life, were applied at least twice a week by the caregivers during critical moments such as staff handover. Repeated measures' analysis of variance and other tests were used to analyze the data. Results Individuals with dementia had a higher wellbeing after the Music Mirror use across different care situations. While the Music Mirrors were played, individuals with dementia showed more positive than negative emotions at each measurement occasion, but emotion scores did not significantly change over time. After the MM use, caregivers felt better, closer to the person with dementia, and less stressed. Caregivers also reported significant gains at the end of the intervention. However, there were no significant changes in the frequency of the behavioral and psychological symptoms of dementia, care-related burden and relationship quality over time, regardless of the treatment condition. Discussion By incorporating personalized audio-biographical cues into their care routines, the wellbeing of people with dementia was improved as well as it had positive momentary effects on their caregivers. The Music Mirror intervention addresses the preferences and needs of people with dementia and helps build bonds between care-recipients and caregivers. Therefore, Music Mirrors can be seen as a highly adaptive and individualized instrument to improve momentary wellbeing of people with dementia in various care situations during daily life.